PENINGKATAN HASIL BELAJAR MELALUI PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) PADA MUATAN IPS DI SDI OTOMBAMBA - Welu, Felix (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research is class action research (Class Action Research) which aims to improve social studies learning outcomes in class IV SDI Otombamba. The implementation of this research consisted of four stages, namely planning, implementation, observation and evaluation and reflection. The subjects in this research were 27 class IV students at SDI Otombamba, 14 male students and 13 female students. Data on the level of students' understanding of social studies subjects, material on natural appearance and socio-cultural diversity through giving tests at the end of the cycle. Data on student activity during the learning process is obtained from the results of observations filled in on the observation sheet. Data obtained from observations were analyzed qualitatively while data from sociology learning results were analyzed quantitatively. The research results showed that in the first cycle which was completed individually, only 11 students or 40.7% of the 27 students met the minimum completion criteria (KKM). Classically it has not been fulfilled because the average value obtained was 58.7. Meanwhile, in cycle II, 26 students or 96.7% had fulfilled the KKM and classically had been fulfilled, namely the average score obtained was 75.9. In cycle I, student learning outcomes were in the medium category. This means that student learning outcomes regarding subject matter have increased from the medium to high category. Based on the results of the research above, it can be concluded that the learning outcomes of SDI Otombamba students through the application of the Numbered Heads Together (NHT) learning model have increased.